Optomotor Swimming in Larval Zebrafish Is Driven by Global Whole-Field Visual Motion and Local Light-Dark Transitions - Kist, Andreas; Portugues, Ruben (Cell Reports, 2019)
Kist and Portugues use reverse correlation in an optomotor behavioral assay in larval zebrafish to identify the stereotypic filter that elicits swimming. It consists of a forward-moving local light-dark transition alongside global whole-field motion. The luminance profile strongly affects behavioral parameters, and filter-specific activity is spread across the brain.
CRIS-Team Scopus Importer:2019-10-08
Keywords: behavior; functional imaging; optomotor response; visual motion; zebrafish